2022
DOI: 10.3390/jpm12101753
|View full text |Cite
|
Sign up to set email alerts
|

Discovering Breast Cancer Biomarkers Candidates through mRNA Expression Analysis Based on The Cancer Genome Atlas Database

Abstract: Background: Research on the discovery of tumor biomarkers based on big data analysis is actively being conducted. This study aimed to secure foundational data for identifying new biomarkers of breast cancer via breast cancer datasets in The Cancer Genome Atlas (TCGA). Methods: The mRNA profiles of 526 breast cancer and 60 adjacent non-cancerous breast tissues collected from TCGA datasets were analyzed via MultiExperiment Viewer and GraphPad Prism. Diagnostic performance was analyzed by identifying the patholog… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 55 publications
0
6
0
Order By: Relevance
“…Overexpression of PSMB4 promotes the proliferation and survival of breast cancer cells, lleading to an unfavorable prognosis [ 47 ]. The study revealed a significant upregulation in AP1M2, PSMD10, and RPL2 expression in breast cancer tissue compared to normal tissues [ 48 50 ]. RPS27A is overexpressed in breast cancer, enhanceing EBV-encoded LMP1-mediated proliferation and invasion through stabilization of LMP1 [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Overexpression of PSMB4 promotes the proliferation and survival of breast cancer cells, lleading to an unfavorable prognosis [ 47 ]. The study revealed a significant upregulation in AP1M2, PSMD10, and RPL2 expression in breast cancer tissue compared to normal tissues [ 48 50 ]. RPS27A is overexpressed in breast cancer, enhanceing EBV-encoded LMP1-mediated proliferation and invasion through stabilization of LMP1 [ 51 ].…”
Section: Resultsmentioning
confidence: 99%
“…Of the 97 known protein-coding genes at these loci, many of the genes located at, or spanning the peak QTL are known to be associated directly with cancer development, or with cancer associated pathways. For example, Kcnd2, Tspan12, Ing3 and Cped1 located on Chromosome six are known to promote proliferation of breast cancer cells ( Yang et al, 2023 ), be a critical factor for cancer associated fibroblast mediated invasion ( Otomo et al, 2014 ), used as a potential biomarker for CRC/breast cancer ( Kim and Lee, 2022 ; Li et al, 2023 ) or confer oncogenic effects in prostate cancer ( Zhu et al, 2023 ) respectively. Likewise on chromosome 12, expression of Matn3, Osr1, and Nt5c1b have been associated with colon adenocarcinoma, gastric and breast cancer development ( Zhao Z. et al, 2023a ; Chi et al, 2023 ; Gadwal et al, 2023 ); potential use as a biomarker for breast cancer ( Li et al, 2020 ) or promotion of EMT and metastasis in breast cancer ( Wang et al, 2020 ; Li et al, 2021 ) and identified as a cancer testis-antigen in canine malignancies ( Nemec et al, 2019 ) respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, metformin treatment reduced oncogenic miR-21-5p in BC cells, further releasing CAB39L expression and evoking activation of AMPK, which was closely associated with reduced migratory and invasive capacity in BC cell lines [ 28 ]. Moreover, HBA2 was significantly downregulated in BC tissues and displayed excellent diagnostic performance [ 29 ]. DLGAP5 is a microtubule-associated protein and mitotic phosphorylated substrate of Aurora-A.…”
Section: Discussionmentioning
confidence: 99%